INSIGHTS, CHALLENGES, AND NEEDS OF ESP TEACHERS IN THE EFL CONTEXT (Scientific journal of the Fergana State University, 2026)
This article examines the main challenges, needs, and experiences of ESP (English for Specific Purposes) teachers within the EFL (English as a Foreign Language) context. The study was based on an analysis of existing literature from open sources. Findings reveal that ESP teachers face difficulties in conducting needs analysis, developing authentic teaching materials, designing integrated tasks, and implementing effective assessment strategies. The necessity for interdisciplinary collaboration and continuous engagement with field experts is also emphasized. In the context of Uzbekistan, developing specialized professional training programs for ESP teachers is essential for enhancing the overall quality and relevance of English language education.